Misalignment between government planning and budgeting in Limpopo department of economic development, environment and tourism - Mahlatji, Elizabeth Sarona (University of the Witwatersrand, Johannesburg, 2022)
Prior to 1994 in South Africa, strategic planning and budgeting processes were fragmented. However, in the post-1994 democratic dispensation, the South African government introduced certain strategic planning and budgeting reforms. The aim of these reforms was to ensure alignment between government planning and budgeting processes to enhance service delivery, as well as the effective and efficient utilisation of resources. These reforms included the introduction of various policy frameworks, structures, and systems to guide planning and budgeting. The purpose of this research was to assess the factors contributing to misalignment between strategic planning and budgeting and challenges this presents in the execution of government programs in LEDET. The study employed the organisational alignment theory to guide the development of this empirical journey stressing the integration of various functional areas within an organisation to enhance performance. A qualitative research approach was employed and a total of 13 senior and middle management officials within the chosen case study participated in the study. Participants were purposefully sampled for semi-structured interviews so as to provide rich information relevant to the phenomenon under investigation due to the experience and knowledge they possess relating to the subject. A thematic data analysis method was used to analyse the primary data and formulate the themes. Some of the findings of this study indicate that, despite the government reforms to ensure alignment between planning and budgeting, misalignment still persists. This misalignment impacts negatively on effective and efficient utilisation of government resources in terms of budget and achievement of planned developmental programs and projects for improved organisational performance. The study further discovered that misalignment between government planning and budgeting is due to both internal and external factors. Internally, misalignment between planning and budgeting is as a result of parallel processes by planning and budgeting units with no efforts for synchronisation. There is duplication of functions that existed for a long time between the department and some state owned entities which has a bearing on allocation of limited resources. In addition, the study found that evaluations of departmental programs and projects to determine their impact on the plight of the poor people and also to inform future planning and budgeting are not conducted. Furthermore, a lack of strategic leadership contributes to the misalignment between planning and budget, as sometimes things are done just for compliance, rather than for improving the quality of the processes to ensure synchronisation. It may be necessary to deploy effective planning and budgeting processes to enhance alignment, support the evaluation of departmental programs and projects to inform future planning and budgeting
A research report submitted In partial fulfillment of the requirements for the degree: Master of Management in the field of Management and Governance to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2022
Keywords: Planning; Budgeting; LEDET; Government; Organisational alignment theory; MTEF; MTSF; PFMA; NDP; Strategic plan; APP; Constitution; Limpopo; UCTD; SDG-8: Decent work and economic growth